2023
DOI: 10.1177/15423050221147901
|View full text |Cite
|
Sign up to set email alerts
|

Patient Religiosity and Desire for Chaplain Services in an Outpatient Primary Care Clinic

Abstract: Outpatient chaplaincy is a new specialty in healthcare, with a relative paucity of research studies exploring the need for spiritual care interventions in ambulatory settings. Over the past 3 years, our interdisciplinary team at the Duke Outpatient Clinic has piloted the extension of professional spiritual care into this hospital-based resident teaching clinic offering primary care to underserved populations in Durham, NC. In this article, we report the results of a series of surveys that we conducted at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They further refer to the study by Gad et al ( 2022) at a non-faith-based academic hospital in Toledo that found that patients with no religious identity (self-identified as atheist, agnostic, or no religion) were just as likely to want a religious/spiritual conversation initiated by their healthcare provider as religious respondents (Henderson, et al, 2023:82). The findings by Henderson, et al (2023) in their own study supported the above too by noting that they found a strong desire for spiritual care services across all respondents, regardless of their self-reported levels of extrinsic religiosity (Henderson, et al, 2023:86).…”
Section: Inclusive Pastoral Caresupporting
confidence: 54%
See 1 more Smart Citation
“…They further refer to the study by Gad et al ( 2022) at a non-faith-based academic hospital in Toledo that found that patients with no religious identity (self-identified as atheist, agnostic, or no religion) were just as likely to want a religious/spiritual conversation initiated by their healthcare provider as religious respondents (Henderson, et al, 2023:82). The findings by Henderson, et al (2023) in their own study supported the above too by noting that they found a strong desire for spiritual care services across all respondents, regardless of their self-reported levels of extrinsic religiosity (Henderson, et al, 2023:86).…”
Section: Inclusive Pastoral Caresupporting
confidence: 54%
“…People across different spheres of life, especially when facing life threatening situations, do need pastoral care of some sort or other. Henderson, et al (2023) note that newer studies demonstrate that the spiritual needs for chaplain care are indeed strong across patient populations, even in non-religious patients. They further refer to the study by Gad et al ( 2022) at a non-faith-based academic hospital in Toledo that found that patients with no religious identity (self-identified as atheist, agnostic, or no religion) were just as likely to want a religious/spiritual conversation initiated by their healthcare provider as religious respondents (Henderson, et al, 2023:82).…”
Section: Inclusive Pastoral Carementioning
confidence: 99%
“…The desire for chaplain support regarding mental health concerns and interpersonal conflict varies across the low-and high-religiosity populations. As the article notes, those who "spend time in private religious activities are very interested in spiritual care to help with mental health concerns (65.6%) and interpersonal conflict (80%) (Henderson et al, 2023)." The low-religiosity population reported less interest in spiritual care in those areas, but "even patients who rarely or never spend time in private religious activities desire chaplain help for several circumstances.…”
mentioning
confidence: 99%
“…Over half of respondents in the very low-religiosity group still desire chaplain support when they are near dying (53.9%) or when they would like prayer (52.3%). Just under 50% (48%) would want help to make sense of suffering" (Henderson et al, 2023).…”
mentioning
confidence: 99%